Molecular and Cellular Biology of the Crayfish Spermatozoon: Toward Development of Artificial Reproduction in Aquaculture - Farhadi, Ardavan; Harlioglu, Ayse Gul (Taylor & Francis Inc, 2019)
In recent decades, crayfish farming has been developing quickly in several regions of the world. Molecular and cellular studies of crayfish spermatozoon provide valuable information regarding the complex reproduction process in this economically and ecologically important animal group. In the present study, the morphology of spermatophore and immotile spermatozoon, post-mating spermatophore storage, morphological and molecular changes during spermatozoon capacitation, acrosome reaction (AR), egg activation, and spermatozoon-egg binding mechanism in crayfish are discussed and compared with the available information in the other members of crustacean decapods. This review shows that there are still gaps in the knowledge on the AR and AR inducers in crayfish. This review summarizes the available information in the field, highlights gaps, and paves the road for development of techniques for artificial reproduction of crayfish.
Keywords: Acrosome reaction; fertilization; gamete; morphology; sperm